Hubungan Profil Lipid Dengan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus: Relationship between Lipid Profile and Blood Glucose Levels in Diabetes Mellitus Patients - Puspitasari, Puspitasari; Aliviameita, Andika (Medicra (Journal of Medical Laboratory Science/Technology), 2018)
Diabetes mellitus is disease caused by a disorder of glucose metabolism. At present, diabetes mellitus is health problem in the world. Increased blood glucose levels can increase the risk of complications of various organs, one of which is cardiovascular disease. This study aims to determine the relationship between cholesterol total levels and triglycerides with blood glucose levels in patients with diabetes mellitus. This type of research is observational analytic with cross sectional design. A total of 45 samples were selected selectively at Aisyiyah Siti Fatimah Tulangan Hospital in January 2016-February 2018. The results of multiple linear regression analysis showed a statistically significant relationship between total cholesterol levels and blood glucose (b = 0,607; p = 0,046), and triglyceride levels with blood glucose levels (b = -0,276; p = 0,003). Based on the results, we found a stati